2017
DOI: 10.1038/oncsis.2017.74
|View full text |Cite
|
Sign up to set email alerts
|

Growth-induced stress enhances epithelial-mesenchymal transition induced by IL-6 in clear cell renal cell carcinoma via the Akt/GSK-3β/β-catenin signaling pathway

Abstract: Stromal cell populations in the tumor microenvironment (TME) play a critical role in the oncogenesis and metastasis of renal cell carcinoma. In this study, we found that there are α-smooth muscle actin positive (α-SMA (+)) cells in the stroma of clear cell renal cell carcinoma (ccRCC) tissues, and their numbers are significantly associated with poor survival in ccRCC patients. Interleukin 6 (IL-6) is a critical diver that induces α-SMA (+) cells in ccRCC tissues via promotion of epithelial to mesenchymal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 44 publications
0
64
0
Order By: Relevance
“…The level of expression of β‐catenin also directly impacts the activation of the Wnt signal pathway . When the degradation of β‐catenin becomes an obstacle, too much β‐catenin accumulates in the endonuclear membrane leading to cancer via an abnormal activation of the Wnt signal pathway . In 2012, Tanya et al reported that the function of Trop2 requires the presence of β‐catenin in nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…The level of expression of β‐catenin also directly impacts the activation of the Wnt signal pathway . When the degradation of β‐catenin becomes an obstacle, too much β‐catenin accumulates in the endonuclear membrane leading to cancer via an abnormal activation of the Wnt signal pathway . In 2012, Tanya et al reported that the function of Trop2 requires the presence of β‐catenin in nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Several other alternative set-ups have been developed to apply a defined stress on an entire cell population for prolonged periods of time, by embedding them in agarose [12] or in extracellular matrix [47] or using a transmembrane-based pressure device [48]. The drawback of such devices is that they are not compatible with high-resolution microscopy due to the thickness of the gels or the transwell geometry.…”
Section: Discussionmentioning
confidence: 99%
“…The TGF-β-induced upregulation of α-SMA and CD44 in LX-2 cells was blocked by βelemene [117]. In addition to CD44, α-SMA is produced when fibroblasts are stimulated and is essential for cell movement, tumor development, and invasion [118,119].…”
Section: β-Elemene Alters Inflammation and Thementioning
confidence: 99%